Disconnection of single-phase rooftop PVs after short-circuit faults in residential feeders - Hosseinian Yengejeh, H.; Shahnia, Farhad; Islam, Syed (Engineers Media Pty, 2016)
© 2016 Engineers Australia.This paper presents an analysis on the disconnection time of single-phase rooftop photovoltaic systems (PVs), located in a three-phase four-wire low voltage distribution feeder, after a single-phase and a three-phase short-circuit fault on the low-voltage feeder. The paper aims to evaluate and discuss the disconnection time and disconnection sequence of PVs in a network with 100% PV penetration level to evaluate the islanding issues that are related to the safety of people and the damage of electrical apparatus. The impact of different parameters such as the location of the fault, impedance of the fault and the ratio of PVs generation capacity to the load demand are contemplated in the analysis. Furthermore, the influence of the network earthing in the form of multiple earthed neutral and non-effectively grounded systems are evaluated on the PVs disconnection time. This research intends to figure out the conditions under which the PVs in the feeder may fail to disconnect after a single-phase or three-phase fault and continue to feed the fault.